2014
DOI: 10.1111/jiec.12095
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Flow of Alloying Elements in Steel during Recycling of End‐of‐Life Vehicles

Abstract: SummaryAlloying elements in steel add a wide range of valuable properties to steel materials that are indispensable for the global economy. However, they are likely to be effectively irretrievably blended into the steel when recycled because of (among other issues) the lack of information about the composition of the scrap. This results in the alloying elements dissipating in slag during steelmaking and/or becoming contaminants in secondary steel. We used the waste input-output material flow analysis model to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 41 publications
1
118
0
1
Order By: Relevance
“…Around 50% of the light shredder residue contains a combustible portion that can be thermally treated. Although there are new technologies that enable sorting and using up to two-thirds of the mass of the shredder residue, in practice, approximately 67% of the remains, after the shredding process, are landfilled [20][21][22][23][24]. It is noted that the materials derived from shredding process cannot be classified as reusable.…”
Section: Shreddingmentioning
confidence: 99%
“…Around 50% of the light shredder residue contains a combustible portion that can be thermally treated. Although there are new technologies that enable sorting and using up to two-thirds of the mass of the shredder residue, in practice, approximately 67% of the remains, after the shredding process, are landfilled [20][21][22][23][24]. It is noted that the materials derived from shredding process cannot be classified as reusable.…”
Section: Shreddingmentioning
confidence: 99%
“…Second, the critical materials are commonly aggregated together into the non-ferrous metal sector, or to even higher levels. Disaggregation of individual metal sectors in IO tables, as shown by Hawkins et al (2007), Nakamura et al (2008), Nakajima et al (2013), Ohno et al (2014), has been done at the country level, but requires very detailed data that are usually not available for critical metals on the global scale. Moreover, MRIO tables represent oneyear snapshots of the world economy or short historic time series only, and there is no standard procedure for how to extrapolate these tables into the future.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Ohno et al ( 2014 ) showed that considerable amounts of alloying elements, which correspond to 7-8 % of the annual consumption in electric arc furnace (EAF) steelmaking, are unintentionally introduced into EAFs. This type of analysis is an interesting application of MFA to help development of more appropriate recycling systems.…”
Section: Metals In Wastementioning
confidence: 99%
“…Some studies discuss alloying elements in metal recycling (Nakajima et al 2011(Nakajima et al , 2013Nakamura et al 2012 ;Ohno et al 2014 ). For example, Ohno et al ( 2014 ) showed that considerable amounts of alloying elements, which correspond to 7-8 % of the annual consumption in electric arc furnace (EAF) steelmaking, are unintentionally introduced into EAFs.…”
Section: Metals In Wastementioning
confidence: 99%